Eradicing Corruption Requires Ethics, Religion And Love As Basic Capital For Accountant - Grana Koeswardani; Sri Trisnaningsih (International Journal of Economics and Management Sciences, 2024)
Corruption has become a serious problem that threatens national stability and progress. Transparency in identifying corruption is becoming increasingly important. This article explores the importance of ethics, religion and conscience as fundamental tools for citizens in efforts to fight corruption. With ethics, religion, and its implications for national and regional government. Ethics strengthens professional integrity, while religion provides moral guidance. Love for the profession, company, and community is also an important motivator for living a life of integrity. Through a combination of these factors, trust can become an effective agent of change in preventing corruption. Helping build a more just, transparent and integrity society by maintaining ethical, religious and loving values ​​in business and accounting practices. Thus, strengthening these values ​​in the accounting profession will have an important positive impact on the progress and prosperity of the nation and state.